The increased adhesion of tumor cells to endothelial cells after irradiation can be reduced by FAK-inhibition - Nguemgo Kouam, Pascaline (Radiat Oncol, 2019)
BACKGROUND: Radiotherapy is administered in more than 60% of all solid tumors. Most patients are cured but a significant number develops local recurrences or distant metastases. The question arises if irradiation might influence the metastatic process. In the present study we examined whether the adhesion of glioblastoma or breast cancer cells to endothelial cells, an important step in metastasis, is affected by photon irradiation. METHODS: U-87 MG, U-373 MG and MDA-MB-231 cancer cells as well as primary human endothelial cells were irradiated with 0, 2, 4, or 8 Gy photons at a dose rate of 5 Gy/min. The adhesion of cancer cells to endothelial cells was tested either with the Vybrant based assay via fluorescent labelling or with an ibidi pump system able to mimic the physiological blood flow in vitro. In addition, the impact of FAK (focal adhesion kinase) inhibitor PF-573, 228 on the adhesion of non-irradiated and irradiated tumor cells was analyzed. Adhesion related and regulated proteins were analyzed by Western blotting. RESULTS: The cellular adhesion was increased after irradiation regardless of which cell type was irradiated. The FAK-inhibitor was able to reduce the adhesion of non-irradiated cells but also the irradiation-induced increase in adhesion of tumor cells to endothelium. Adhesion related proteins were enhanced after irradiation with 4 Gy or 8 Gy in both cells types. The increased adhesion after irradiation is accompanied by the phosphorylation of src (Y416), FAK (Y397) and increased expression of paxillin. CONCLUSION: Irradiation with photons in therapeutic doses is able to enhance the interaction between tumor cells and endothelial cells and by that might influence important steps of the metastatic process.